A guide to the procurement of privately financed projects an indicative assessment of the procurement process - Lamb, Douglas (Thomas Telford, 2004)
This guide outlines the concept of privately financed projects (PFP) that can be used for both public-private and private-private interactions. Utilising models from many countries the guide develops a robust procurement system applicable to PFP and project finance in both the EU and overseas.
Keywords: Public contracts.; Public works -- Finance.; Public-private sector cooperation.; elektronické knihy; electronic books